Pengaruh Motivasi terhadap Kinerja Pegawai pada Kantor Badan Penanggulangan Bencana Daerah Kabupaten Sidenreng Rappang - A. Putri Nabila; Gazali Amin; Dian Nirmasari (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the influence of motivation on employee performance at the Regional Disaster Management Agency (BPBD) Office of Sidenreng Rappang Regency. Motivation is seen as one of the fundamental factors in human resource development because it can encourage increased work morale, effectiveness, and efficiency in carrying out employee duties and responsibilities. Highly motivated employees will be encouraged to work more disciplined, creative, and productive, so that they can make a positive contribution to the achievement of organizational goals, especially in public service and disaster management.nThis study uses a quantitative approach with a survey method. The sampling technique chosen is a saturated sample, namely all employees and honorary personnel at BPBD Sidenreng Rappang Regency are made respondents. This consideration is made because the population is relatively small so that it can be reached as a whole. The research data was collected using a questionnaire compiled based on indicators of work motivation and employee performance, then analyzed using a simple regression test to determine the relationship and influence between variables.nThe results showed that the calculated t value of 2.167 was greater than the t table of 2.048 at a significance level of 5%. This proves that there is a positive and significant influence between motivation on employee performance. Motivation contributes 15.7% to performance improvement, while the rest is influenced by other factors such as work discipline, work environment, competence, and leadership. Nevertheless, these findings emphasize that motivation continues to play an important role as the main driver of employee performance.nThus, increasing motivation through the provision of awards, incentives, and continuous coaching can be an important strategy in strengthening the quality of performance of BPBD employees in Sidenreng Rappang Regency.